Genomic and non-genomic actions of estrogen on synaptic plasticity in SH-SY5Y cells - Siriporn Chamniansawat (2018)
Estrogen modulates synaptic plasticity, an important mechanism of memory storage. Previously, we have reported that estrogen rapidly increases the expression of Arc (activity-regulated cytoskeleton associated protein), a key protein for synaptic plasticity, via non-genomic phosphoinositide-3 kinase (PI-3K)-, mitogen-activated protein kinase (MAPK)-, and estrogen receptor (ER)-dependent pathways in SH-SY5Y cells. The present study aimed to investigate the role of each ER subtype, α and β, in synaptic plasticity in SH-SY5Y cells. The specific agonist of ERβ (DPN) markedly induced Arc expression that mimics treatment with estrogen, but not ERα (PTT). Determination of subcellular localization of ERβ using immunocytochemistry shows that ERβ was retained in the cytoplasm of the untreated cells. In estrogen-treated cells, the membrane and cytosolic ERβ gradually decreased, while nuclear ERβ progressively increased in time-dependent manner, suggesting estrogen-dependent nuclear translocation of ERβ. Nuclear accumulation of ERβ at 6-12 h post-estrogen treatment, leads to increased PSD-95 and SYP mRNA expression, indicating the classical genomic estrogenic action on synaptic plasticity. However, the block of PI-3K signaling by Wortmannin partially suppressed estrogen (48 h)-induced PSD-95 and SYP expression, suggesting a crosstalk mechanism between genomic and non-genomic actions of estrogen on synaptic plasticity. Therefore, the estrogen-enhanced synaptic plasticity is ERβ-dependent and involves the crosstalk mechanism of non-genomic and genomic estrogenic actions. © 2009 Elsevier Ireland Ltd. All rights reserved.